Cow talk : understanding dairy cow behaviour to improve their welfare on Asian farms - Moran, John, 1945-; Doyle, Rebecca; CSIRO (Clayton South, VIC : CSIRO Publishing, 2015)
The aim of this manual is to improve the welfare of dairy cattle in tropical developing countries, and by doing so to optimise cow and herd performance. It gives the stockmen and farmers directly concerned with the cattle a better understanding of animal behaviour and the ways cattle communicate their comfort or distress. The book discusses normal cattle behaviour and shows how domestication and breeding can affect behaviour to achieve high levels of production of milk, live weight gain and fertility.
Chapter 1: Introduction -- Chapter 2: Cow welfare -- Chapter 3: The implications of cattle domestication -- Chapter 4: Cattle behaviour -- Chapter 5: Observing cow signals -- Chapter 6: Quantifying cow signals -- Chapter 7: Cow comfort -- Chapter 8: Auditing cow welfare -- Chapter 9: Stock management on Asian small holder dairy farms -- Chapter 10: A protocol for the welfare of stock on tropical small holder dairy farms -- Chapter 11: Conclusions.
Includes bibliographical references (pages [229]-232) and index.
Keywords: Dairy cattle -- Behavior; Cattle -- Behavior; Cows -- Behavior; Animal welfare -- Asia; Australian